(untitled) (Global Journal of Human-Social Science, 2025)
The analysis focuses on the construction of a "diasporic literary phenomenon," in which mythology, politics, and poetry intersect within a narrative that translates the listening to racialized and territorialized bodies in the Brazilian hinterlands (sertão). The discussion is guided by the hypothesis that the textual construction represents a subjective-objective process in which the author acts as an ethno-translator. From this perspective, the crossroads is explored as a symbolic and epistemological category, and literature as a form of social mediation. The crossroads, in this sense, materializes the entanglement of multiple temporalities, identities, and knowledge systems present in the narrative, reinforcing the author’s role as a mediator between the lived experience of sertão communities and their literary representation.